Clinical Characteristics According to Sensitized Allergens in Adult Korean Patients With Bronchial Asthma - Jung, Jae Woo; Choi, Jae Chol; Shin, Jong Wook; Kim, Jae Yeol; Park, In Won; Choi, Byoung Whui (Allergy, asthma & immunology research, 2010)
Allergic sensitization is a risk factor for the development of bronchial asthma. This study was conducted to investigate clinical manifestations according to sensitized allergens in adult Korean patients with bronchial asthma. In total, 523 adult patients who were diagnosed with bronchial asthma between March 2002 and March 2008 were included in the study. All patients underwent skin prick tests for approximately 45 allergens or a specific IgE test. Sensitized allergens were grouped into the following categories: house dust mites, fungus, pollen, and animal dander. Atopy was defined as a positive skin prick test response or the presence of a specific IgE to one or more allergens. Of the 523 patients, 295 (56%) were sensitized to one or more allergens. A younger median age, greater proportion of males, higher eosinophil counts, and higher total IgE levels were observed in the atopic asthma group compared to the non-atopic asthma group. The PC20 value was negatively correlated with eosinophil counts and total IgE in the atopic asthma group. In the subgroup analysis, patients sensitized to Cladosporium showed poorer pulmonary function and a higher response to bronchodilators. In addition, patients sensitized to Alternaria showed severer bronchial hyperresponsiveness than non-atopic patients with asthma. Finally, a gradual increase in the number of sensitized allergens was noted with increasing age, eosinophil counts, and total IgE levels. We suggest the need for identifying the existence of atopy and exact offending allergens at the time of asthma diagnosis, since significant differences in sex, age, blood test results, and lung function were observed according to atopy and sensitized allergens.